Scholars committed to opportunities in psychological education: a training and mentoring program for future psychologists of color. Issue 1 (1st January 2020) - Fix, Rebecca L.; Silverstein, Madison W.; Nuhu, Nadratu; Gray, Wendy N.
ABSTRACT: Although strides towards inclusivity and racial equality have been made in graduate education, many barriers to graduate education remain for racial/ethnic minorities. In response, we created Scholars Committed to Opportunities in Psychological Education (SCOPE), a mentor-based program for racial/ethnic minority undergraduates. 63 racial/ethnic minority undergraduates completed the SCOPE curricula and pre- and post-program questionnaires regarding graduate school application knowledge, application confidence, stress, self-efficacy, and SCOPE program satisfaction. Mentors completed a training and questionnaires in one SCOPE cohort. Knowledge about the GRE, the application process, and application confidence increased, and stress decreased, following SCOPE. The result of this work is a portable mentoring program that can be used across disciplines and demographics to increase inclusivity and equality.